PENINGKATAN NILAI TAMBAH PADA PERUSAHAAN PENGGILINGAN BERAS DI KABUPATEN KONAWE - Suharjo, Suharjo (EDUTECH CONSULTANT, 2019)
Rice is a staple food for most of the Indonesian population so that rice cannot be separated from the lives of Indonesian people, both in cities and in rural areas. Since 1984 Indonesia has been able to self-sufficient in rice. However, lately there have been various obstacles in self-sufficiency. A study by the Indonesian Agency for Agricultural Research and Development reveals that rice is a strategic commodity because it plays an important role in the economy and national food security, so it must be the main base in revitalizing agriculture in the future. In line with the increase in population, the need for rice in the 2005-2025 period is projected to continue to increase due to an average population growth rate of 1.7% per year. The purpose of this study was to determine the process of procurement, processing and marketing of rice, assessing the added value obtained by the milling business in a milling company in Konawe Regency. The population in this study were 10 Milling Companies. The results showed that the added value obtained by the milling business in Konawe District in the processing and marketing of rice was Rp. 725.33 / kg with a value added ratio of 15.05%, a margin of Rp. 918 / kg, a profit rate of 94.49. Other input contributions need to be reduced so that the capital owner's profit can be maximized